Spiritual transformation: Reaching and equipping Sub-Saharan African children - Johannes J. Knoetze (In die Skriflig, 2015)
Whenever a person engages with a child, the engagement is not neutral – it is ‘for better or for worse’. A fair question would be why Christians must reach and equip Africa’s children for spiritual transformation. By giving a missional perspective in an attempt to answer the question, this article wants to contribute to the development of an African child and youth theology. In the first part of the article, a specific understanding of theology and how it is practised, is described. Understanding and reaching children are put within a specifictheological and missiological understanding also of the local faith community. From a missiological perspective the second part of the article makes use of Christian anthropology to understand Africa’s children’s context and how the local faith community can equip them spiritually. The third part deals with the concept of spiritual transformation as a process, and the role of the local faith community within this process.